2013
DOI: 10.1371/journal.pone.0084039
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Socially-Assigned Ethnicity, Racial Discrimination and Health Advantage in New Zealand

Abstract: BackgroundWhile evidence of the contribution of racial discrimination to ethnic health disparities has increased significantly, there has been less research examining relationships between ascribed racial/ethnic categories and health. It has been hypothesized that in racially-stratified societies being assigned as belonging to the dominant racial/ethnic group may be associated with health advantage. This study aimed to investigate associations between socially-assigned ethnicity, self-identified ethnicity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 24 publications
1
38
1
Order By: Relevance
“…In this context, concordance between self-identified and socially assigned race was greatest among individuals who self-identified as European (97.6%, which is considered the dominant ethnic group) and Asians (92.7%). Discordance was highest among individuals who self-identified as Māori, Pacific, and those who identified as multi-ethnic [25]. In a study conducted across several Latin American countries, interviewers reported their assessment of respondent's race/ethnicity according to the following 5 categories: white (blanca/branca); mixed-white (mestizo/parda), mixed-black (mulato), indigenous (indigena), and black (negra/preta) or other [31].…”
Section: Patterns Of Socially-assigned Race By Race/ethnicitymentioning
confidence: 95%
See 2 more Smart Citations
“…In this context, concordance between self-identified and socially assigned race was greatest among individuals who self-identified as European (97.6%, which is considered the dominant ethnic group) and Asians (92.7%). Discordance was highest among individuals who self-identified as Māori, Pacific, and those who identified as multi-ethnic [25]. In a study conducted across several Latin American countries, interviewers reported their assessment of respondent's race/ethnicity according to the following 5 categories: white (blanca/branca); mixed-white (mestizo/parda), mixed-black (mulato), indigenous (indigena), and black (negra/preta) or other [31].…”
Section: Patterns Of Socially-assigned Race By Race/ethnicitymentioning
confidence: 95%
“…Socially-assigned race studies conducted in New Zealand, included Māori, Pacific peoples, Asian and European ethnic groups [25]. In this context, concordance between self-identified and socially assigned race was greatest among individuals who self-identified as European (97.6%, which is considered the dominant ethnic group) and Asians (92.7%).…”
Section: Patterns Of Socially-assigned Race By Race/ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…26 In this paper, socially ascribed ethnicity refers to participants' perceptions of how they are categorised by others (primarily as either Māori or NZ European) that emerged during face-to-face interviews. Further, thematic analysis accords with the epistemological approach employed in this Kaupapa Māori study as it foregrounds a Māori world-view that explicitly recognises the validity and legitimacy of cultural aspirations of being Māori, and the fundamental right to exercise autonomy over health and wellbeing.…”
Section: Methodsmentioning
confidence: 99%
“…Within the broad overlapping and intersecting themes of age, spatial location at birth, timing of entry into the health system and self-reported perceptions of social ascription as Māori (discussed in more detail elsewhere), 26,28 analysis of participant narratives identified the inability to develop and maintain relational continuity of care with freely chosen and often trusted GPs as a principal barrier to accessing quality and non-discriminatory primary healthcare. Rapid access to any doctor was, however, considered appropriate when consulting with minor or acute problems, for example, by young males with sports injuries.…”
Section: Relational Continuity Of Carementioning
confidence: 99%